"BAD' AL-AMALI" BY USMAN AL-AL-USHI AND ITS SPECIFIC ASPECTS - Ruziev Toir (Scholar Express Journal, 2022)
This article provides information about the Hanafi scholar Sirojiddin Usman Al-Ushi, who lived in Movarounnakhr in the 12th century, and his work " Bad' al-Amali" . Also, the article analyzes the work "Bad'ul Amali" and highlights its position in the Hanafism-Maturid school of kalam and its characteristics.
Keywords: Al-Ushi; Movarounnakhr; aqeedah